Malaysian SMEs Performance and the Government Business Support Service: The Moderating Effects of Absorptive Capacity - Jauriyah Shamsuddin; Mohammad Nizam Sarkawi; Abdul Rahman Jaafar; Noor Fareen Abd Rahim (International Journal of Supply Chain Management, 2017)
The purpose of this study is to test and develop absorptive capacity as a moderator of the relationship between Government Business Support Service (GBSS) and SMEs Performance in Malaysia. A random sampling technique was used on 150 usable questionnaires and data was analysed by SPSS 19. Statistically, the results confirmed that financial and non-financial support by government positively related to SMEs Performance and there is an interaction of absorptive capacity as a moderator on GBSS and SMEs Performance.